Evaluation of Green and Renewable Energy System Alternatives Using a Multiple Attribute Utility Model: The Case of Turkey - Kaya, Ihsan; Kahraman, Cengiz (SPRINGER-VERLAG BERLIN, 2011)
Energy is a critical foundation for economic growth and social progress. It is estimated that 70% of the world energy consumption could be provided from renewable resources by the year 2050 so that renewable energy which is the inevitable choice for sustainable economic growth, for the harmonious coexistence of human and environment as well as for the sustainable development is very important for the humanity. The aim of this chapter is to evaluate the renewable energy alternatives as a key way for resolving the Turkey's energy-related challenges because of the fact that Turkey's energy consumption has risen dramatically over the past three decades as a consequence of economic and social development. In order to realize this aim, the Multi-Attribute Utility Theory (MAUT) is used for the evaluation of renewable energy alternatives. According to MAUT, the overall evaluation U(x) of an object x is defined as a weighted addition of its evaluation with respect to its relevant value dimensions. In the evaluation phase, 4 main attributes and 17 sub-attributes are used to determine the most appropriate renewable energy alternative among Solar, Wind, Hydropower, Biomass, and Geothermal.
Keywords: DECISION-MAKING; MULTICRITERIA ASSESSMENT; POWER-PLANTS; FUZZY-LOGIC; RANKING; MANAGEMENT; ENVIRONMENT; TECHNOLOGY; SIMULATION; SELECTION; Computer Science; Energy & Fuels; Engineering